Evaluating the effectiveness of Tough Fix Hyper additive in improving adhesion and technical properties of asphalt concrete C12.5 in Dong Thap province - Nguyễn, Văn Long; Nguyễn, Minh An (Journal of Transportation Science and Technology, 2026)
This study focuses on evaluating the effectiveness of three adhesion-promoting additives, namely Tough Fix Hyper (TFH), Tafpack-Premium (TPP), and Styrene-Butadiene-Styrene (SBS), when used with bitumen 60/70 and commonly utilized aggregates in Dong Thap province, including Antraco and Tan Cang stones. Experimental results indicate that all three additives significantly enhance the bitumen–aggregate adhesion, improving it from grade 2 to grade 4. Among them, the TFH additive demonstrated outstanding effectiveness, achieving a comparable level of improvement while requiring a significantly lower dosage than the other two additives. Based on the experimental findings, a TFH content of 0.15% was selected to further assess its influence on several technical properties of asphalt concrete C12.5. The results show that the incorporation of TFH markedly increases both Marshall stability and retained stability, thereby enhancing the load-bearing capacity and moisture resistance of the asphalt pavement